RELATIONSHIP OF BODY MASS INDEX AND UPPER ARM CIRCUMFERENCE WITH THE INCIDENT OF ANEMIA IN ADOLESCENT WOMEN AT SMAN 1 MANTEWE TANAH BUMBU DISTRICT YEAR 2023 - Luhur Sartika; Bardiati Ulfah; Darmayanti; Yaolanda Rizqi Agustina (Media Inovasi Pendidikan dan Publikasi, 2024)
Background: Adolescence is a time or period to connect the transition from child to adult. Problems often occur in adolescents, one of which is nutritional problems which cause anemia in adolescents. Purpose: To determine the relationship between body mass index and upper arm circumference with the incidence of anemia in adolescent women at SMAN 1 Mantewe Tanah Bumbu Regency in 2023. Method: This research is an analytical study with a cross sectional design. The data collection technique uses purposive sampling. The sample in this study was 92 teenage women in class 10 of SMAN 1 Mantewe. Statistical test analysis using spearman rho with the help of the SPSS version 25 computerized program. Results: There is a relationship between body mass index and the incidence of anemia in adolescent women at SMAN 1 Mantewe Tanah Bumbu Regency in 2023 with a value of ρ-value = 0.000 < α = 0.05 and There is a relationship between upper arm circumference and the incidence of anemia in adolescent women at SMAN 1 Mantewe Tanah Bumbu Regency in 2023 ρ-value = 0.000 < α = 0.05. Conclusion: The relationship between body mass index and upper arm circumference with the incidence of anemia in adolescent women is a reference for schools to pay attention and carry out nutritional status checks every 6 months.